Modification of Iron Oxide to Promote Reaction Property for Chemical Looping Combustion with CO. Issue 8 (2nd August 2016) - Hu, Song; Chen, Qindong; Xiang, Jun; Su, Sheng; Sun, Lushi; Wang, Yi; Xu, Boyang; Chi, Huanying
ABSTRACT: Oxygen carrier is one of the key roles in the chemical looping process. Thermogravimetric analysis results showed that, among the four metal oxides (Fe2 O3, CuO, NiO, and CaSO4 ), Fe2 O3 possessed the best regenerative capacity although its crystal cell would shrink after one redox reaction. It was found that loading of Fe2 O3 on Al2 O3 could effectively inhibit its crystal cell shrinking and increase Brunauer–Emmett–Teller (BET) surface of particles up to a certain value. Further study showed that BET surface of the particles had a positive relationship with their redox reactivity. When the BET surface area increased by five times, the maximum reaction rate improved about 13% (reduction stage) and 37% (oxidation stage). Fe2 O3 /Al2 O3 oxygen carrier prepared by the sol-gel process contained a new crystal structure, Al3 Fe5 O12, which could improve the recycle stability of the oxygen carrier. The modified oxygen carrier with Fe/Al2 O3 molar ratio 2:1 kept the best regeneration capacity of about 97% after five cycles' redox reaction; at the same time, the oxygen capacity of the sample increased about 25% compared with pure Fe2 O3 .